Предмет: Математика,
автор: katya1200013
х(х+9)=0
(х-8)(х+3.5)=0
(3х+2.7)(4х-13)=0
Помогите решить
Ответы
Автор ответа:
2
Ответ:
вот
Пошаговое объяснение:
1) х(х+9)=0
х1=0 х+9=0
х2=-9
2) (х-8)(х+3.5)=0
х-8=0 х+3.5=0
х=8 х=-3.5
3) (3х+2.7)(4х-13)=0
3х+2.7=0 4х-13=0
3х=-2.7 4х=13
х=-0.9 х=13/4 х=3 1/4
katya1200013:
Спасибочки)
Похожие вопросы
Предмет: Английский язык,
автор: rafida1983
Предмет: Английский язык,
автор: Аноним
Предмет: Другие предметы,
автор: Denis010203
Предмет: История,
автор: dianatuskeeva9
Предмет: Английский язык,
автор: Денис121009